2014
DOI: 10.1371/journal.ppat.1004424
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from Hepatitis C Infected Patients Transmit HCV Infection and Contain Replication Competent Viral RNA in Complex with Ago2-miR122-HSP90

Abstract: Antibodies targeting receptor-mediated entry of HCV into hepatocytes confer limited therapeutic benefits. Evidence suggests that exosomes can transfer genetic materials between cells; however, their role in HCV infection remains obscure. Here, we show that exosomes isolated from sera of chronic HCV infected patients or supernatants of J6/JFH1-HCV-infected Huh7.5 cells contained HCV RNA. These exosomes could mediate viral receptor-independent transmission of HCV to hepatocytes. Negative sense HCV RNA, indicativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
373
2
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(392 citation statements)
references
References 60 publications
12
373
2
5
Order By: Relevance
“…Further evidence for virion-independent genome shuttling was provided recently in a study that employed a set of cells with resistance to different antibiotics to distinguish between true EV-mediated RNA transfer and cell-cell fusion (42). Szabo's group, meanwhile, provided an important step toward understanding the in vivo relevance of the phenomenon, finding infectious exosomes in blood of HCV patients (43). Those authors also reported that viral RNA in exosomes was complexed with Argonaute 2 (Ago2) and the replication-enhancing host miR-122 (43).…”
Section: Common Transport Mechanisms Of Evs and Virusesmentioning
confidence: 99%
“…Further evidence for virion-independent genome shuttling was provided recently in a study that employed a set of cells with resistance to different antibiotics to distinguish between true EV-mediated RNA transfer and cell-cell fusion (42). Szabo's group, meanwhile, provided an important step toward understanding the in vivo relevance of the phenomenon, finding infectious exosomes in blood of HCV patients (43). Those authors also reported that viral RNA in exosomes was complexed with Argonaute 2 (Ago2) and the replication-enhancing host miR-122 (43).…”
Section: Common Transport Mechanisms Of Evs and Virusesmentioning
confidence: 99%
“…In other cases, EVs provide an "envelope" to nonenveloped viruses, e.g., hepatitis A, and these EV-encapsulated viruses can infect cells (5). Similarly, EV released by hepatitis C-infected cells can carry fully infectious viral genomes that in target cells generate new infectious viral particles (6).…”
mentioning
confidence: 99%
“…It has been recently shown that HCV hijacks exosomes to incorporate infectious RNA into these structures that are then capable of mediating receptor-independent transmission of the virus (32,39). Here, we describe another model for subversion of exosome-like structures to mediate receptor-independent transmission involving the novel bunyavirus SFTS virus.…”
Section: Discussionmentioning
confidence: 97%
“…It has been previously shown that hepatitis C virus (HCV) hijacks secreted vesicles for receptor independent transmission of viral RNA (32,39). Furthermore, hepatitis A virus (HAV) is released cloaked in host membranes in a release mechanism resembling , and isolation of extracellular microvesicles was performed as depicted in Fig.…”
Section: Sfts Virus Infection Induces the Formation Of Cytoplasmic Stmentioning
confidence: 99%